2011
DOI: 10.1007/s12031-011-9672-6
|View full text |Cite
|
Sign up to set email alerts
|

The SDF-1 3′A Genetic Variation of the Chemokine SDF-1α (CXCL12) in Parallel with its Increased Circulating Levels is Associated with Susceptibility to MS: A Study on Iranian Multiple Sclerosis Patients

Abstract: Immune system-related factors are important in pathogenesis of multiple sclerosis. The CXC chemokine SDF-1α (CXCL12) is involved in the immune responses. Hence, the aim of this study was to investigate the association between serum levels of SDF-1α (CXCL12) and its gene polymorphisms at position +801 with multiple sclerosis. In this experimental study, blood samples were collected from 100 multiple sclerosis patients and 100 healthy controls on EDTA pre-coated tubes. DNA was extracted and DNA samples were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Astrocytes are also the source of CXCL10 in both human and mouse EAE models [29,59,78], and evidence from these models demonstrates that both TNF-α and IFN-γ (as members of the proinflammatory cytokines) regulate CXCL10 expression in cell lines [79] as well as a rat model [48]. …”
Section: Role Of Cxcl10 In Msmentioning
confidence: 99%
“…Astrocytes are also the source of CXCL10 in both human and mouse EAE models [29,59,78], and evidence from these models demonstrates that both TNF-α and IFN-γ (as members of the proinflammatory cytokines) regulate CXCL10 expression in cell lines [79] as well as a rat model [48]. …”
Section: Role Of Cxcl10 In Msmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report of CXCL12 level in serum of PD patients. Azin et al reported that CXCL12 serum level in Iranian MS patients was significantly higher than controls [21]. In contrast, a reduction in CXCL12 serum levels has also been shown in early Alzheimer’s disease (AD) [22].…”
Section: Discussionmentioning
confidence: 99%
“…Stromal cell-derived factor-1 (SDF-1; known as CXCL12 in the recent chemokine nomenclature) is described as a CXC chemokine [unpubl. data and [16][17][18]. This biological compound is involved in chemotaxis and it is active on T lymphocytes and monocytes but does not affect neutrophils.…”
Section: Introductionmentioning
confidence: 98%
“…More recent reports indicate that the serum and/or tissue expression of CXCL12 is increased in various autoimmune diseases, including MS [unpubl. data and 2, 18,19 ]. Therefore, it appears that the genetics of CXCL12 may be altered in MS and other autoimmune inflammation-related disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation